Design and optimization of photonic crystal fibre THz bio‐sensor for extremely impressible identification of dengue - Abu Hena Mohammad Iftekharul Ferdous; Mohammad Rasel Miah; Khalid Sifulla Noor; Mohammad Asaduzzaman; Mohammad Azizul Haque; Mosammot Momtahina Bani; Diponkar Kundu; Mohammad Feroz Ali (IET Nanodielectrics)
Abstract The detection of human diseases is a major application for biosensors. During this work, a 2D photonic crystal fibre (PCF) biosensor design for dengue virus detection has been suggested. This work presents the decagonal hollow core PCF‐based dengue virus bio‐sensor and quantitatively investigates it over the terahertz regime. The suggested biosensor's performance is assessed using COMSOL Multiphysics, a professional tool that uses the Finite Element Method. The simulation's outcomes show that the suggested sensor performed better than earlier research, with a high sensitivity of 98.79%, 97.96%, 97.71%, 98.58%, 96.99% and 97.47% with more less confinement loss 1.2766 × 10−12 dB/m, 1.6385 × 10−12 dB/m, 2.8015 × 10−13 dB/m, 1.1798 × 10−13 dB/m, 7.0336 × 10−12 dB/m and 0.00 dB/m respectively for infected Haemoglobin (Hgb), Normal Haemoglobin (Hgb), Infected Platelets (Plt), Normal Platelets (Plt), Infected Plasma (Psm) and Normal Plasma (Psm) at 3.0 THz using the ideal geometric configuration. Very soon, its remarkable sensitivity and guiding capabilities will be crucial to dengue virus detection technology.